PSIKOEDUKASI OPTIMALISASI PENGETAHUAN GURU TENTANG ADHD - Dewinta Ariani; Iriani Indri Hapsari; Kahfi Hizbullah; Yufiarti; Atikah Ainun Mufidah (Jendela Akademika, 2026)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental condition commonly found in school-aged children. However, many teachers still have a limited understanding of ADHD and how to manage students with this condition effectively. Such limitations may reduce the support provided for students and hinder their academic and social development. To address this issue, a community service program was conducted in the form of psychoeducation for teachers. The program aimed to increase teachers’ knowledge of ADHD characteristics, early identification, classroom behavior management, and collaboration with parents and professionals. The activities included interactive lectures, case study discussions, and simulations of inclusive learning strategies. Participants were actively engaged throughout the sessions and showed increased awareness of ADHD and its implications for the learning process. Pre- and post-program evaluations indicated a measurable improvement in participants’ understanding, with the average pre-test score of 89.9 increasing to an average post-test score of 97.2, representing a 7.27% improvement. While most teachers were already aware of ADHD symptoms, they reported needing clearer guidance on practical steps for intervention and classroom application. This community service activity demonstrates that psychoeducational programs can effectively strengthen teachers’ capacity to create more inclusive, supportive, and conducive learning environments, providing students with ADHD greater opportunities for optimal academic and social growth.